PENGARUH PROGRAM KESEJAHTERAAN KARYAWAN TERHADAP MOTIVASI KERJA KARYAWAN PT BANK SULSELBAR KANTOR PUSAT MAKASSAR - Megawaty Megawaty (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2017)
Objectives The research conducted by the authors is to analyze the Employee Benefit Effect on Employee Motivation in PT. Sulselbar Bank Head Office Makassar. The study was conducted at PT. Bank Head Office South Sulawesi Makassar. The analytical method used is descriptive kualiltatif by using multiple linear regression analysis. Result analysis and discussion shows that the Welfare Program significantly influence employee motivation at PT. Sulselbar Bank Head Office Makassar.